2001
DOI: 10.1128/jb.183.2.500-511.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Horizontal Transfer of Ssu DAT1I Restriction-Modification Genes to the Streptococcus suis Genome

Abstract: Different strains of Streptococcus suis serotypes 1 and 2 isolated from pigs either contained a restrictionmodification (R-M) system or lacked it. The R-M system was an isoschizomer of Streptococcus pneumoniae DpnII, which recognizes nucleotide sequence 5-GATC-3. The nucleotide sequencing of the genes encoding the R-M system in S. suis DAT1, designated SsuDAT1I, showed that the SsuDAT1I gene region contained two methyltransferase genes, designated ssuMA and ssuMB, as does the DpnII system. The deduced amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 61 publications
5
58
0
1
Order By: Relevance
“…1). The codon usage patterns for the sly and orf102 genes were not anomalous compared to those previously reported for purine and cysteine biosynthetic genes (26,32). No transposable element or long-repeat sequence was found in the 5,545 or 4,257-bp sequence.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…1). The codon usage patterns for the sly and orf102 genes were not anomalous compared to those previously reported for purine and cysteine biosynthetic genes (26,32). No transposable element or long-repeat sequence was found in the 5,545 or 4,257-bp sequence.…”
mentioning
confidence: 51%
“…However, there are several variants of these markers and some S. suis isolates from diseased pigs do not possess one or more of them (1,3,4,13,19,38,41), indicating genetic heterogeneity with respect to these markers. Recently, it was shown that some S. suis strains possess a type II restriction-modification (R-M) system, designated SsuDAT1I, which is an isoschizomer of Moraxella bovis MboI (10), whereas some other strains lack the system (32). Nucleotide sequence comparison between strains having the SsuDAT1I system and those lacking the system revealed that the SsuDAT1I system was originally inserted into the S. suis chromosome from a foreign source by illegitimate recombination and was subsequently transferred among S. suis strains by homologous recombination (31,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All isolates were stored in Luria-Bertani (Becton Dickinson) broth containing 30 % glycerol at 280 uC and minimally passaged for the experiments to avoid changing key traits including capsule production. In addition, S. suis strains S735 (NCTC 10234; serotype 2 reference strain) and 204 (serotype 1 field isolate) (Sekizaki et al, 2001) were used for the production of rabbit antiserum, and S. suis strain 89/1591, isolated from a pig with septicaemia (Salasia et al, 1995), and its isogenic unencapsulated mutant (CPS2B) (Okura et al, 2011) were used to compare their phenotypic characteristics with other encapsulated and unencapsulated cps2J-positive isolates. Enterococcus faecalis NCTC 775 was used as a control for PCR scanning analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An RM system can transpose into a new locus (264). It can simply insert into an operon-like gene cluster (like in the pur operon in Streptococcus suis [265]) or insert with a short or long and variable target duplication (such as an 8-bp sequence when type II RM genes insert into Xanthomonas oryzae pv. oryzae [247] or a 506-bp-long direct duplication after insertion of a type IIS system in Helicobacter pylori [266]).…”
Section: Genetic Elements Controlling the Stability Of Mobile Elementsmentioning
confidence: 99%